The nexus between Narcissist Followers and Leaders-Antecedent for Toxic Leadership - Dorasamy, Nirmala (Journal of Economics and Behavioral Studies, 2018)
Increasingly, it is recognized that organizations have toxic leaders, who harm organizational success. While they harm organizational success, it can be argued that followers who collude are also contributors to such harm. Literature increasingly points to the interrelationship between leaders and organizations and its impact on organizational success. Notably absent is the systematic examination of the toxic relationship between leaders and followers as colluders and its impact on organizational success. The purpose of the paper is to examine the extent to which followers as colluders reinforce toxic leadership through the relational aspects. The focus is on active, destructive and unethical leaders within the negative leadership continuum, since it is difficult to claim that behaviours representing passiveness and incompetence are equally negative. Through a relational approach to leadership study, the situated commonality between leaders and followers is explored to show that manifestations of narcissism in both leaders and followers who collude in perpetuating toxic leadership can cause organizations to drift into failure. The paper does not consider leadership in any organizational or situational context. The study’s methodology contributes to the objective of the research. The use of a qualitative research method was useful in arguing the exhibitionism of narcissism not only among leaders, but also followers. This method aligns with the purpose of the study. There is a paucity of literature on how the relational aspects of the leader-follower dynamic influence the toxic leadership/ followership reality. The relevancy of the study not only contributes to the literature on toxic leadership, but more specifically showing how narcissist followers as colluders influence narcissist leaders in a toxic leadership relationship. By examining the toxic leader/ follower relationship, a richer understanding of toxic followers can possibly emerge. This is important, since leaders do not produce results alone, together with the followers they contribute to the well-being of the organization. A range of practitioner research articles and published empirical research articles were reviewed to highlight narcissism among toxic leaders and elaborate on the destructive role of followers who reinforce toxic leadership through support. The analysis shows that while leaders and followers as colluders can cause harm to organizational outcomes, the extent of the harm can be largely influenced by the nature of the narcissist traits commonly endorsed by both. The paper highlights an overall framework that may help to identify the major considerations needed to mitigate the harmful effects of the narcissist leader/ follower relationship on positive organisational outcomes. Further, the paper suggests examining the relational aspects of leaders and followers as colluders, especially by looking at the impact of various narcissist traits that potentially strengthen the toxic relationship between the leader and follower. Finally, it is recommended that the proposed guidelines be tested in an empirical paper to measure their effectiveness.